Effect of Additional Stabilities (CMC) and Citric Acid in Red Guava Juice (Psidium Guajava L.) - Ahmad Syauqi Firdaus; Rima Azara (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of adding a stabilizer (CMC) to guava juice and to determine the effect of adding citric acid to guava juice. this research was conducted at the laboratory of product development and food analysis of the food technology study program, faculty of science, and technology, university of Muhammadiyah Sidoarjo from October to December 2021 using a factorial randomized design on guava juice. the first factor is the concentration of CMC namely (0,2%, 0,5% and 0,7%), the second factor is the concentration of citric acid, namely (0,2%, 0,3% and 0,4%). the organoleptic test was analyzed using the Friedman test. the results showed that the concentration of CMC and citric acid had a significant difference from the results for the texture organoleptic test. the best treatment was guava juice with a CMC concentration of 0.7% and citric acid concentration of 0.4% which showed an aroma organoleptic test of 3.00 (ordinary), texture organoleptic test of 3.30 (usual-like), and taste organoleptic test of 2.90 (dislike- usual), color organoleptic test 3.17 (usually-like).